The Long Non-coding RNA lnc-DMP1 Regulates Dmp1 Expression Through H3K27Ac Modification - Xia, Xin; Ruan, Yi; Li, Boya; Yu, Yansong; Kong, Xiangbo; Zhuang, Peilin; Wu, Hong (Frontiers in Genetics, 2020)
Several long noncoding RNAs (lncRNAs) have been reported regulate the expression of neighbor protein-coding genes at post-transcriptional, transcriptional and epigenetic levels. Dentin matrix protein 1 (DMP1), a noncollagenous extracellular matrix protein, plays an important role in dentin and bone mineralization. However, the transcriptional regulation of lncRNA on Dmp1 has not been reported. In this study, we identified a novel lncRNA named lnc-DMP1, which is near the Dmp1 gene region and undergoes remarkable changes during mandible development. Lnc-DMP1 is co-localized and significantly expressed correlation with Dmp1 in embryonic and postnatal mouse mandibles. In MC3T3-E1 cells, lnc-DMP1 positively regulates DMP1 expression and skeletal mineralization.Moreover, lnc-DMP1 induces the activity of Dmp1 promoter by modulating H3K27Ac enrichment in the promoter region of Dmp1. In conclusion, our results indicate that lnc-DMP1 is a novel lncRNA near the Dmp1 gene region and regulates the DMP1 expression by modulating the H3K27 acetylation level of the Dmp1 promoter.